2019
DOI: 10.1109/access.2019.2930664
|View full text |Cite
|
Sign up to set email alerts
|

Security and Reliability Performance Analysis of Cooperative Multi-Relay Systems With Nonlinear Energy Harvesters and Hardware Impairments

Abstract: In this paper, we investigate the reliability and security performance of cooperative multi-relay systems, where both source and relay nodes are energy-constrained nonlinear energy harvesters, scavenging energy from a power beacon nearby. Our analysis is based on practical model since residual hardware impairments (RHIs) and channel estimation errors (CEEs) are considered. Aiming at improving the system efficiency, three representative relay selection strategies are considered: 1) random relay selection (RRS);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…The same definitions for ς p,q , λ q below (39) are valid in terms of ϕ q in (43) and (44). Lastly, substituting (38), (40), (42) and (44) into (36), the ABEPs of users are derived as in (45) and (46), as shown at the bottom of this page.…”
Section: Bit Error Probability (Bep)mentioning
confidence: 99%
“…The same definitions for ς p,q , λ q below (39) are valid in terms of ϕ q in (43) and (44). Lastly, substituting (38), (40), (42) and (44) into (36), the ABEPs of users are derived as in (45) and (46), as shown at the bottom of this page.…”
Section: Bit Error Probability (Bep)mentioning
confidence: 99%
“…Since the broadcast characteristic of wireless transmission, the IoT networks are more vulnerable to attack by illegal users, thus, wireless communication urgently requires a communication network with a higher degree of information security [13]. As the basis of communication networks, information security is showing unprecedented importance [14].…”
Section: Introduction a Backgroundmentioning
confidence: 99%
“…By introducing multi-antenna into the NOMA systems, it can achieve the advantages of multi-antenna and NOMA. Therefore, some research works have investigated the combined technology; see [34][35][36][37][38] and the references therein. Authors in [34] studied the performance of multiple-antenna NOMA and OMA, and it indicated that the performance of multiple-antenna NOMA outperforms that of multiple-antenna OMA one.…”
Section: Introductionmentioning
confidence: 99%
“…The antenna selection (AS) technology has the advantages of low cost, low complexity, high diversity gains, which can solve the computational complexity and power consumption issues caused by multiple antennas. Therefore, the combination of NOMA and AS has attracted significant attention [35][36][37][38]. In [35], the authors analyzed the secure outage performance of MISO-NOMA systems by deriving the exact analytical expressions of SOP under optimal antenna selection (OAS) and suboptimal antenna selection (SAS) schemes, and proposed an effective power allocation scheme to obtain the non-zero diversity order under the two AS schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation